Intermolecular coulombic decay in biology: the initial electron detachment from FADH- in DNA photolyases - Harbach, Philipp H. P.; Schneider, Matthias; Faraji, Shirin; Dreuw, Andreas (The journal of physical chemistry letters, 2013)
Intermolecular coulombic decay (ICD) is an efficient mechanism of low-energy electron generation in condensed phases and is discussed as their potential source in living cells, tissues, and materials. The first example of ICD as an operating mechanism in real biological systems, that is, in the DNA repair enzymes photolyases, is presented. Photolyase function involves light-induced electron detachment from a reduced flavin adenine dinucleotide (FADH-), followed by its transfer to the DNA-lesion triggering repair of covalently bound nucleobase dimers. Modern quantum chemical methods are employed to demonstrate that the transferred electron is efficiently generated via a resonant ICD process between the antenna pigment and the FADH- cofactors.
Gesehen am 18.12.2017